Potential Antagonists Trichoderma viride as Biofungicide, Plant Spacing, and Agricultural Lime Application to Suppress Anthracnose on Chili - Tasrif, Arifin; Yuliar, Yuliar; Sulistyowati, Dwiwanti; Krisnawati, Endang; Adirianto, Bayu; Sugiharti, Dwi (Jurnal Perlindungan Tanaman Indonesia, 2024)
Anthracnose caused by Colletotrichum capsici and C. gloesporium on chili is a disease that can reduce chili yields up to 80%. Control with fungicide has not been able to provide maximum results, because Colletotrichum can spread due to splashing of water, especially in the rainy season. The use of antagonistic fungi against Colletotrichum spp. has been widely published but is still limited to the laboratory and greenhouse scale, while field conditions are unpredictable. This study aims to identify the potency of Trichoderma viride that can be used as a biofungicide to control anthracnose in chili and to determine aspects of agronomic that can reduce the risk of anthracnose in chili. Samples of infected plants of stems, leaves, and fruits were collected from experimental farm of Bogor Agricultural Development Polytechnic. The experiment was conducted using Randomized Complete Design and Randomized Complete Block Design. The percentage of disease intensity of the fungus C capsici and the intensity of anthracnose in chili both under screen house and open fields. While testing the effect of cultivation aspects using different types of fertilizer on plant height, fruit weight, number of fruits, and the percentage of disease intensity of Colletotrichum spp. were analyzed. The results of this study shown that four isolates of fungi have been identified such as Penicillium sp., Aspergillus flavus, T. viride, and C. capsici. In vitro analysis shown the ability of T. viride to suppress the growth of the C. capsici  up to 71%. The fungus T. viride with a density of 7×106 CFU/mL can suppress the development of anthracnose by 59 to 87% under screen house conditions. However, under field conditions, the fungus T. viride was not able to suppress the development of anthracnose. Agronomic aspects such as plant height, number of fruits and production, and productivity of chili were not significantly effect on anthracnose.